Policing America's educational systems - Watts, John Harrison (Routledge, 2019)
The evolution of policing in K-12 public education -- Criminal procedure and law within the context of an educational environment -- The school resource officer (SRO) -- Public school district police departments -- Risk assessment at the college campus -- Investigating crime on a college campus -- Active shooter/hostile event (ASHE) awareness and response -- A review of campus shootings -- Concealed carry on campus -- Understanding crime on campus -- Explanations of crime on campus based on theory -- Safe schools are no accident : prosocial development is key -- The future of policing in education.